2018
DOI: 10.1016/j.geotexmem.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tensile/compressive strength ratio of fibre reinforced cemented soils

Abstract: The present work proposes a theoretical model for predicting the splitting tensile strength (qt)-unconfined compressive strength (qu) ratio of artificially cemented fibre reinforced soils. The proposed developments are based on the concept of superposition of failure strength contributions of the soil, cement and fibres phases. The soil matrix obeys the critical state soil mechanics concept, while the strength of the cemented phase can be described using the Drucker-Prager failure criterion and fibres contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 42 publications
1
13
0
3
Order By: Relevance
“…Observing that both the porosity and the quantity of cement influenced the mechanical behavior of cemented materials, Consoli et al (2007) developed a rational dosage methodology for soilcement considering the porosity/cement index (η=C iv ), defined as the porosity of the compacted mixture (η) divided by the volumetric content of cement (C iv ). Subsequent works (e.g., Consoli et al 2009Consoli et al , 2010Consoli et al , 2011Consoli et al , 2012Consoli et al , 2017Consoli et al , 2018Fonseca et al 2009;Festugato et al 2017Festugato et al , 2018Marques et al 2014;Henzinger et al 2018) confirmed that the η=C iv ratio is a reliable parameter to predict the mechanical properties of soil-cement mixtures (q u , q t , G 0 , c 0 , ϕ, durability, among others). The porosity/cement index performs an essential part in estimating the predicted q u because it considers both the amount of porosity and the amount of cement.…”
Section: Different Approach To the Authors' Resultsmentioning
confidence: 91%
“…Observing that both the porosity and the quantity of cement influenced the mechanical behavior of cemented materials, Consoli et al (2007) developed a rational dosage methodology for soilcement considering the porosity/cement index (η=C iv ), defined as the porosity of the compacted mixture (η) divided by the volumetric content of cement (C iv ). Subsequent works (e.g., Consoli et al 2009Consoli et al , 2010Consoli et al , 2011Consoli et al , 2012Consoli et al , 2017Consoli et al , 2018Fonseca et al 2009;Festugato et al 2017Festugato et al , 2018Marques et al 2014;Henzinger et al 2018) confirmed that the η=C iv ratio is a reliable parameter to predict the mechanical properties of soil-cement mixtures (q u , q t , G 0 , c 0 , ϕ, durability, among others). The porosity/cement index performs an essential part in estimating the predicted q u because it considers both the amount of porosity and the amount of cement.…”
Section: Different Approach To the Authors' Resultsmentioning
confidence: 91%
“…Diambra and Ibraim (2015), Diambra et al (2017), and Festugato et al (2018) also pointed out the similarity between Eq. (2) and equations such as Eq.…”
mentioning
confidence: 69%
“…Based on the concept of superposition of failure strength contributions of the soil and cement phases, Diambra et al (2017Diambra et al ( , 2018) provided a theoretical derivation for the unconfined compressive strength of artificially cemented granular soils. Based on this derivation, Festugato et al (2018) proposed an extended theoretical modeling framework to predict the compressive and tensile strengths of fiber-reinforced artificially cemented soils by considering the individual properties of the soil matrix, the cementing phase, and the fibers. The material granular matrix follows concepts of the critical state soil mechanics and the strength of the cemented phase is described by the Drucker-Prager failure criterion.…”
mentioning
confidence: 99%
“…An approach is necessary to analyze and evaluate the performance of lightweight materials and to design new lightweight materials [13][14][15][16]. The performance of a lightweight material can be measured by two key parameters: density and effective elastic modulus.…”
Section: Introductionmentioning
confidence: 99%